Review of the Elmidae of Ecuador with the description of ten new species (Coleoptera: Elmidae) - Monte, Cinzia; Mascagni, Alessandro (Zootaxa, 2012)
Material collected during a biodiversity expedition in some protected areas of Ecuador, located in the provinces of Coto-paxi, Pichincha and Napo, resulted in ten new species and three first records. The new taxa are: Cylloepus bartolozzii sp.nov., Cylloepus cesari sp. nov., Cylloepus fabianorum sp. nov., Cylloepus francescae sp. nov., Cylloepus mazzai sp. nov.,Cylloepus terzanii sp. nov., Cylloepus whitmanae sp. nov., Macrelmis elicioi sp. nov., Pharceonus cianferonii sp. nov.and Stenhelmoides onorei sp. nov. The three records are: Cylloepus vicinus Hinton, 1940, Hexacylloepus nirgua Hinton,1973, Phanocerus congener Grouvelle, 1898. Habitus photographs and illustrations of aedeagi for all the new taxa andother useful characters for some of them, a key to the graniger species-group of Macrelmis, and a checklist of the Ecuadorian species with their general and local distributions are hereby included.